Inhibition of T cell responses by activated human CD8+ T cells is mediated by interferon-gamma and is defective in chronic progressive multiple sclerosis. - K E Balashov; S J Khoury; D A Hafler; H L Weiner (The Journal of Clinical Investigation, 1995)
The autologous mixed lymphocyte reaction (AMLR) involves the activation of T cells by autologous antigen presenting cells. Cells are generated during the course of the AMLR that have suppressive properties in vitro. In the present study we investigated the induction of CD8+ T cells in the AMLR with suppressive properties and the mechanism by which these cells downregulate in vitro proliferative responses. Purified CD8+ but not CD4+ T cells activated in the AMLR in conditioned medium inhibited proliferation of autologous T cells by anti-CD3 or PPD. Nonactivated CD8+ T cells did not suppress. The CD8+ T cells activated in the AMLR in the presence of conditioned medium (CD8+ Tact) were CD11b negative and were noncytotoxic. The inhibitory effect of CD8+ Tact cells was completely abrogated by anti-IFN-gamma antibody, but not by anti-IL-4, anti-IL-10, or anti-TGF-beta antibody. The induction of CD8+ Tact cells in the AMLR was blocked by anti-IL-2 or by anti-GM-CSF antibody and the combination of these two recombinant cytokines could support the induction of suppressive CD8+ Tact cells. CD8+ Tact cells were defective in patients with chronic progressive multiple sclerosis (MS) as compared to patients with relapsing-remitting MS or normal controls. Our studies provide a basis for understanding the mechanism of suppression by human CD8+ T cells in terms of specific cytokines, and demonstrate the potential importance of these cells in a human autoimmune disease as their function is defective in patients with progressive MS.